Billboards of the United States of America and Nazi Germany in 1942: Propaganda and War - Ortiz-Arellano, Edgar (2022)
During World War II, in the context of the war confrontation between German National Socialism and the liberal democracy of the United States of America (USA), propaganda was instrumental in conveying messages that inspired the population of those countries in conflict. Billboards were ideal instruments to promote the recruitment of soldiers to their armies, sustain the war effort and clearly identify enemies. This article addresses the cases of the US and Nazi Germany, with the aim of analyzing the billboards from 1942, their connection with textuality and the dissemination of their ideological interests related to war action. It is concluded that there are similarities in both cases in the racial types used in the images, as well as the leading role of the texts found in the billboards.